Study the Effect of Cordyceps militaris Supplement in the Diet on Growth Performance of Japanese Quail - Rahab Asmer (Basrah Journal of Veterinary Research)
the aim of studying the effect of the Cordyceps militaris supplement in the feed on the growth performance of Japanese quail. This study used 180 unsexed Japanese quail chicks, one day old and with an initial weight of 10.3 - 8.8 grams. They were randomly distributed into 4 treatments. Each treatment had three replicates, and each replicate had 15 chicks in cages containing a battery. The current study included experimental period from (1-42) days for the chicks. The transactions were as follows: T1: Control treatment (without any addition), T2: Treatment of adding Cordyceps militaris 1 mg/kg feed, T3: Treatment of adding Cordyceps militaris 2 mg/kg feed.T4: Treatment of adding Cordyceps militaris 4 mg/kg feed. Production characteristics were measured, such as average weekly live body weight and average weekly feed consumption. The weekly and cumulative weight gain rate and the weekly and cumulative food conversion factor. The results of this study showed the following: The highest significant difference (P ≤ 0.05) was obtained for adding the Cordyceps militaris fungus 4 mg/kg feed in the average weekly live body weight, the cumulative weight gain rates, rate of cumulative feed consumption &The rate of feed conversion factor recorded a significant improvement of Japanese quail compared to the other treatments and the control group that recorded the lowest levels in this trait